EXPLORING WORDING AND MEANING OF CONTEMPORARY SERMONIC DISCOURSE - Aleksandra Bizjak Koncar; Helena Dobrovoljc (European Scientific Journal, ESJ, 2014)
The theoretical construct for the present paper is provided by Hasan’s concept of genre (1984). Her model of identification of genre, which is based on Halliday’s semantically driven model of language description, makes it possible to convey and specify the rich complexities at play between the discourse, semantic and lexico-grammatical levels for the genre under consideration. We apply the theory to nine English contemporary sermons. We focus our analysis on the relationship between wording and meaning. In order to exemplify this interrelationship in actual texts belonging to a particular genre we analyse one sermon in detail. By using semantic networks for entity and event it is possible to state semantic properties of functional elements that distinguish sermons from other genres. We then discuss the generic characteristics of sermons and show how the method of argumentation, which is based on everyday experiences or appeals to human feelings, leads the believers towards a Christian life-style and faith.